Analisis Penanganan Foreign Object Debris (FOD) Oleh Petugas Apron Movement Control (AMC) Dalam Menjaga Keamanan Dan Keselamatan Penerbangan Di Bandara Udara Internasional Adi Soemarmo Boyolali - Lala Rahmandhani; Hodi (Institut Nalanda, 2023)
Foreign Object Debris/ Damage (FOD) is a foreign object or hazardous material in the runway and apron area that has the potential to pose a hazard to aircraft safety and operations. AMC Apron Movement Control Officers, Ground Handling, as well as Flight operators Namely Line Maintenance, or other units working in the airside area must participate in maintaining cleanliness in the apron area. This aims to create smooth activities on the air side.This study uses qualitative research methods, where data collection is carried out by interviews, observation, documentation. This study aims to find out what are the obstacles experienced by Apron Movement Control (AMC) officers in handling Foreign Object Debris (FOD) and to find out what impacts can occur related to Foreign Object Debris (FOD) in the apron area of Adi Soemarmo Boyolali International Airport The results of this study are the constraints faced by Apron Movement Control (AMC) unit officers at Adi Soemarmo international airport, the number of human resources in the AMC unit cannot cover the area of the apron, the lack of awareness of operational officers in the Apron area, especially in order and cleanliness, and the number of violations carried out by operational officers in the Apron area of Adi Soemarmo International Airport and damage caused by Foreign Object Debris (FOD) is a major problem in the aviation maintenance industry which can affect the level of aircraft safety.